The Class of 1939 with Ship's Officers - Campus History Collection (California Maritime Academy)
First row: Left to Right: J. M. Boyer, H. C. Dupuis, Mr. E. L. Robberson, Mr. E. C. Miller, Mr. B. M. Dodson, Mr. R. M. Sheaf, Dr. r. G. Benson, Mr. George Barkely, Captain N. E. Nichols, Mr. J. M. Cadwell, Mr. David Warwick, Mr. J. G. Ellis, Mr. C. G. Hansen, L. L. Buwalda, L. T. White. Second Row: Left to right: W. A. Smith, R. B. Simpson, W. W. Fell, C. K. Holzer, R. N. Hargis, G. R. Kilburn, N. W. Bird, W. D. Sype, R. M. Maehle, S. J. Drummond, G. A. Nagle, N. B. Young, F. L. Martin. Third Row: Left to right: E. A. Yates, P. Jensen, C. W. Audet, G. S. Twitchell, H. L. Leichel, W. J. Williams, C. A. Krauchi, W. F. Averill, J. M. Hendy, H. M. Wilson, D. D. McElroy, J. L. Boyce, A. H. Blodgett. Top Row: Left to right: K. W. Clark, J. M. Clawson, D. A. Dancy, A. R. Sims, S. W. Grabowski, A. J. Erickson. Absent are: Chief Engineer R. C. Dwyer, H. A. Frey, T. S. Fostiak.